Speciation in a keystone plant genus is driven by elevation: a case study in New Guinean Ficus - Segar, S T; Volf, M; Zima Jnr, J; Isua, B; Sisol, M; Sam, L; Sam, K; Souto-Vilarós, D; Novotny, V (Journal of evolutionary biology, 2017)
Much of the world's insect and plant biodiversity is found in tropical and subtropical 'hotspots', which often include long elevational gradients. These gradients may function as 'diversity pumps' and contribute to both regional and local species richness. Climactic conditions on such gradients often change rapidly along short vertical distances and may result in local adaptation and high levels of population genetic structure in plants and insects. We investigated the population genetic structure of two species of Ficus (Moraceae) along a continuously forested elevational gradient in Papua New Guinea. This speciose plant genus is pollinated by tiny, species-specific and highly coevolved chalcid wasps (Agaonidae) and represented by at least 73 species at our study gradient. We present results from two species of Ficus sampled from six elevations between 200 m and 2700 m a.s.l. (almost the entire elevational range of the genus) and 10 polymorphic microsatellite loci. These results show that strong barriers to gene flow exist between 1200 m and 1700 m a.s.l. Whereas lowland populations are panmictic across distances over 70 km, montane populations can be disjunct over 4 km, despite continuous forest cover. We suggest that the limited gene flow between populations of these two species of montane Ficus may be driven by environmental limitations on pollinator or seed dispersal in combination with local adaptation of Ficus populations. Such a mechanism may have wider implications for plant and pollinator speciation across long and continuously forested elevational gradients if generalist insect pollinators and vertebrate seed dispersers also form populations based on elevation.
Keywords: Wasps; Pollination; Gene Flow; Ficus; sršňovití; Papua New Guinea; gene flow; Animals; biodiverzita; tok genů; opylení; mutualism; zvířata; pollination; Papua Nová Guinea; mountains; Biodiversity